Distribución y uso de hábitat de Thamnophis pulchrilatus (Cope, 1855) en Chignahuapan, Puebla, México - González-Hernández, Adriana; Moro-Hernández, Dulce M.; Cruz, J. Alberto (Instituto de Ecología, A.C., 2016)
We report the second record of Thamnophis pulchrilatus in the State of Puebla, and the first record of arboreal behavior for the species and second for the genus. In addition, we provide natural history data for this snake species.